Midsubstance Vastus Lateralis Tear in the Young Athlete: Case Report and a Review of the Literature. Issue 3 (22nd May 2023) - Miles, Rebecca N.; Schroeder, Jeremy D.; Creech, Julie A.; Hulsopple, Chad; Higgins, David L.
Abstract: Vastus lateralis tendon tear is an infrequent cause of lateral knee pain. Previously reported cases have described acute injury in middle-aged men after eccentric quadriceps contraction. This case report discusses 2 adolescent patients with longitudinal midsubstance tears diagnosed with MRI and dynamic ultrasound and treated successfully with operative intervention.